Urban local authorities and the delivery of micromobility strategies obstacles in the implementation of bicycle hire in the UK - Dudley, G; Banister, D; Schwanen, T (Alexandrine Press, 2021)
The pressures on urban local authorities to deliver mobility strategies highlight both their need and ability to connect problems and solutions, and then successfully implement the schemes. These difficulties are compounded by other distinctive pressures, from both above and below. From above there can be pressures from national government to deliver strategies, but at the same time not necessarily be provided with the necessary financial and political resources. From below, there can be an attraction towards innovators who can provide strategies at apparently little or no cost to the public sector. These relationships can be unpredictable and unstable, while the technologies themselves can display weaknesses, and be subject to change. The dynamics of the delivery of micromobility can therefore offer strong challenges to urban local authorities in constructing stable networks, mobilizing public support for their actions, and in linking in with other transport services. The two case studies selected here cover the development of bicycle hire in the UK, with particular reference to dockless bicycle hire. Even when the local authorities have active intentions to oversee successful innovations, they are unlikely to succeed without the stronger involvement of central government, including the necessary statutory powers, together with adequate financial resources and associated expertise.